(untitled) (EAAE Annual Conference Proceedings, 2019)
Creativity is a mental process, as Andreasen (2006) describes, it happens when a thought comes up to surface in the mind, it has a complex nature and it does not happen in a tabula rasa condition, instead interaction of human thoughts with socio-cultural situations creates this phenomenon, as Portillo (1996) defines the creativity as an interconnected and multidimensional construct involving person, process, product and place (environment/ press). One of the main intentions of this paper is to address the relationship between the creativity and its supportive environment in case of architectural education which can be defined as a design study that get its origins from creativity.